Prevalence of computer vision syndrome and associated ocular morbidity in a tertiary care hospital - Chaudhary, Aparajita; Rai, Arpita; Singh, S. P.; Singh , Vibha (International Journal of Research in Medical Sciences, 2023)
Background: This study was done to determine the prevalence of computer vision syndrome and associated ocular morbidity in a tertiary care hospital. Methods: A cross sectional observational study was conducted on 673 patients based on the inclusion criteria. The patients were asked to fulfil the computer vision syndrome survey form 3 and OSDI questionnaire. Spontaneous eye blink rate, Schirmer’s test 1, tear break up time, refraction were performed for these patients. Data was collected and analysed by SPSS software. Results: The prevalence of computer vision syndrome was 73% with 294 males and 206 females. The mean age of the patients was 30.29 years. Most of the participants were between 21-30 years. The screen time for most of the study participants (59.80%) came out to be >6 hours/day on average. The chief complaint of majority patients was blurred vision and asthenopia whereas the secondary complaint was watering and headache. Maximum patients (38.20%) from our study were students and competitive exam aspirants followed by teachers and software engineers. The screen modality used by 34.20 % patients was mobile phones > laptops. The mean SEBR was 13.50 minutes. The mean OSDI was 17.44. The screen time was significantly correlated to SEBR (p<0.0001). Also the screen time and OSDI correlation came out to be significant (p<0.0001). Conclusions: The present study revealed a significantly high prevalence of CVS among our patients. The ocular symptoms are predominantly affecting the convergence power of eyes and tear film instability causing blurred vision and dryness.